Social Unionism in Hard Times: Union-Community Coalition Politics in the CAW Windsor’s Manufacturing Matters Campaign - Ross, Stephanie (Labour / Le Travail, 2011)
Abstract As many of the traditionally unionized sectors of the economy experience crisis, unions are turning to social unionist strategies of coalition-building and community mobilization as a means of defending jobs through external solidarity. This paper explores the politics and dynamics of the Canadian Auto Workers’ (caw) organization of a union-community coalition and rally in Windsor, Ontario as a means of defending the manufacturing base. The paper contends that while Windsor’s May 2007 Manufacturing Matters rally was quite successful in its short-term aims, due to the caw’s strong mobilizing structures and longstanding relationships between local unions and community organizations, internal coalition dynamics and framing processes led to decisions which limited the longer-term capacities of the campaign. The coalition opted to emphasize place over class as the unifying element, to produce non-adversarial discourses and tactics so as to avoid appearing anti-business, and to marginalize more militant talk and tactics. These outcomes raise questions about both the sustainability for ongoing solidarity and mobilization amongst the Windsor working class, and the capacity of the local labour movement to articulate counter-hegemonic interpretations of economic problems and promote policy options not dominated by the needs and interests of economic and political elites.